2019
DOI: 10.1186/s13568-019-0936-9
|View full text |Cite
|
Sign up to set email alerts
|

Serotype distribution, antimicrobial susceptibility, antimicrobial resistance genes and virulence genes of Salmonella isolated from a pig slaughterhouse in Yangzhou, China

Abstract: Salmonella is an important food-borne pathogen associated with public health and high economic losses. To investigate the prevalence and the characteristics of Salmonella in a pig slaughterhouse in Yangzhou, a total of 80 Salmonella isolates were isolated from 459 (17.43%) samples in 2016-2017. S. Derby (35/80, 43.75%) was the most prevalent, followed by S. Rissen (16/80, 20.00%) and S. Newlands (11/80, 13.75%). The highest rates of susceptibility were observed to cefoxitin (80/80, 100.0%) and amikacin (80/80,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 44 publications
3
13
0
Order By: Relevance
“…Here in our study also, we have recovered a few isolates showing the same resistance pattern, which is alarming. Higher level of resistance to Ampicillin and Tetracycline reported by many workers (Li et al 2019) corroborated with the present ndings. Salmonella Enteritidis causes gastroenterological disorders in human and their antimicrobial resistance is a huge concern.…”
Section: Discussionsupporting
confidence: 93%
“…Here in our study also, we have recovered a few isolates showing the same resistance pattern, which is alarming. Higher level of resistance to Ampicillin and Tetracycline reported by many workers (Li et al 2019) corroborated with the present ndings. Salmonella Enteritidis causes gastroenterological disorders in human and their antimicrobial resistance is a huge concern.…”
Section: Discussionsupporting
confidence: 93%
“…FIGURE 3 | Heatmap of the detection of antimicrobial resistance genes among the studied Salmonella isolates (n = 78). Zhou et al, 2017) and in Spain (39.7%) (Arguello et al, 2012), while they were higher than those reported in the slaughtered pigs in Sardinia, Italy (12.9%) (Fois et al, 2017); pig carcasses and intestines from five slaughterhouses in Belgium (14.1%) (De Busser et al, 2011); a pig slaughterhouse in Yangzhou, China (17.43%) (Li et al, 2019); pork and slaughterhouse environment in Ahmedabad, Gujarat, India (13.7%) (Chaudhary et al, 2015); and pig slaughterhouses in two different regions of southwestern Spain (12.93%) (Morales-Partera et al, 2018). According to the slaughtering process, samples recovered from the dehairing area and splitting area were the most contaminated samples.…”
Section: Discussionmentioning
confidence: 63%
“…These isolates belong to five different serovars and six MLST patterns, namely, with importance degree, Salmonella Typhimurium ST19, Salmonella Typhimurium ST34, Salmonella London ST155, Salmonella Rissen ST469, Salmonella Goldcoast ST358, and Salmonella Derby ST40. In China, Salmonella Derby was identified as the most isolated serovar from pig slaughterhouse samples (Li et al, 2016(Li et al, , 2019Zhou et al, 2017Zhou et al, , 2018Liu et al, 2020). However, Salmonella Typhimurium has been reported previously as the dominant serovar in Salmonella isolates recovered from pig slaughterhouses in Henan Province (Bai et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that Salmonella is widely drug resistant and commonly multidrug resistant [ 66 ], especially with commonly used antibiotics such as tetracycline and trimethoprim. Tetracycline resistance occurs most often by the acquisition of genes that encode efflux pumps such as tet genes [ 67 ].…”
Section: Discussionmentioning
confidence: 99%